A simple game-theoretical framework for studying R&D expenditures and R&D cooperation - Ulrich Kaiser (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2001)
This paper derives a three stage Cournot duopoly game for research collaboration, research expenditures and product market competition. The amount of knowledge firms can absorb is made dependent on their own research efforts, e.g. firms? absorptive capacity is treated as an endogenous variable. It is shown that cooperating firms invest more in R&D than non?cooperating firms if spillovers are sufficiently large. The degree of market competition is a key determinant of the effects of research cooperation on research efforts, implying that existing models which assume perfect competition might be too restrictive.
Keywords: O31; 330; research cooperation; research expenditures; knowledge spillovers